Quasi-Optimal Tool Trajectories for High Speed 2.5D Process Based on Morphological Transformation. (December 2020) - Xu, Ke; Li, Yingguang; Yang, Mengyuan
Abstract: 2.5D processes are ubiquitous in pocket machining of structural parts as well as layer based additive manufacturing. Modern manufacturing systems are mostly integrated with high-speed motion capacity, which conventionally generated tool path cannot fully exploit due to large path stepover variation and sharp turnings at degenerated corners. Advanced geometric approaches strived to increase the local smoothness of the trajectory without taking care of the stepover variation, which could cause uneven material deposition in layered additive process and excessive load impact in cutting process. To liberate the high-speed capacity in 2.5D process, we developed a brand new scheme for tool trajectory planning, by taking advantage of image morphology. A morphological transformation of the target 2D shape, termed medial core, is defined and identified in this paper, which serves crucially to generate stepover constrained tool paths. The utilization of medial core facilitates a parameterization of the 2D shape, where qualified iso-curves can be easily propagated to satisfy in the high speed context. By comparing with other state-of-the-art tool path generation methods, our method outperformed in both additive process and cutting process, with noticeably reduced processing time, better surface quality in additive process and stabilized milling force in pocket cutting process. Highlights: An image based path generation scheme is proposed for high-speed machining and additive manufacturing process. Proposed medial core transformation of an arbitrary 2D shape leads to controllable stepover variation of the path. Smoothed path is generated via proposed morphological parameterization rather than using regular offsetting method. The proposed scheme exhibits high scalable performance in both additive and subtractive highspeed processes.